The complex effects of retirement on health - Andreas Kuhn (IZA World of Labor, 2018)
Retirement offers the opportunity to give up potentially risky, unhealthy, and/or stressful work, which is expected to foster improvements in retirees' health. However, retirement also bears the risk that retirees suffer from the loss of daily routines, physical and/or mental activity, a sense of identity and purpose, and social interactions, which may lead them to adopt unhealthy behaviors. Depending on the relative importance of the different mechanisms, retirement may either improve or cause a deterioration of retirees' health, or eventually have no effect on it at all.
Keywords: I10; I12; J14; J26; 330; retirement; mental and physical health; mortality; health behavior; reverse causality; heterogeneous effects